Transnational activism and the Israeli-Palestinian conflict - Hallward, Maia Carter 1976- (Palgrave Macmillan, 2013)
"This book examines the polarization of positions surrounding the transnational boycott, divestment, and sanctions (BDS) movement aimed at ending the Israeli occupation. The vast discrepancy in portrayals of the movement - framed alternately as a nonviolent movement for freedom and human rights and as a form of war by other means - is intriguing, and the passion on both sides of the issue suggests the tactic is powerful and resonates deeply. Drawing on first-hand interviews with activists and opponents, press coverage, and organizational materials, this book systematically compares four cases of BDS activism in the United States, using an analytical framework that draws from the literature of social movements, nonviolent resistance, discourse analysis, and contentious politics. It will be of interest to students, scholars, policy makers, and activists"..